Association between depressive symptoms and social support in a nationally representative sample of older adults (ELSI-Brasil) - Beatriz Oliveira Carvalho; Érico Castro-Costa; Maria Fernanda Lima-Costa; Antônio Ignácio de Loyola Filho (Brazilian Journal of Psychiatry)
Objective: To investigate the association between depressive symptoms and social support among a representative sample of the Brazilian population aged 50 years or older. Methods: Cross-sectional study of 8,074 participants of the second wave of the Brazilian Longitudinal Study on Aging (ELSI-Brasil). Depressive symptoms were screened with the Center for Epidemiologic Studies Depression Scale (CES-D8) instrument, and social support was investigated in its structural and functional dimensions. Sociodemographic variables and health conditions were considered for adjustment in investigating the association between social support and depressive symptoms using the Poisson regression model. Results: The prevalence of depressive symptoms was estimated at 19.1% (95%CI 16.7-21.7). In the analysis adjusted for possible confounding factors, depressive symptoms were independently associated with negative social support in the items “not married” (prevalence ratio [PR] = 1.24; 95%CI 1.07-1.44), “not having someone to trust” (PR = 1.31; 95%CI 1.10-1.56) and “not having someone to borrow money or an object from, in case of need” (PR = 1.46; 95%CI 1.21-1.75). Conclusion: The present findings highlight the importance of social relations in determining the presence of depressive symptoms and reinforce the need to implement public policies aimed at strengthening social networks to minimize this public health problem.